Allium cepa assay based comparative study of selected vegetables and the chromosomal aberrations due to heavy metal accumulation - Sabeen, Maria (Saudi J Biol Sci, 2020)
Irrigation of industrial effluents may end in the bioaccumulation of various toxic metals and consequent genetic changes in contaminated food crops. To test this hypothesis and extent of genetic modifications, Allium cepa test was performed to food crops viz. tomato (Lycopersicum esculentum) and chili (Capsicum annum) as Allium cepa test is a useful tool to assess genetic variations in plants. Prior to A. cepa test, the plants were exposed to various metal concentrations 125–1000 mg/L in the synthetic wastewater. The extracts of harvested plants were used to grow the root of A. cepa following its standard method. The root tips were fixed, stained and examined under compound microscope (almost 300–400 dividing cells) to check the extent of chromosomal variations during various stages of mitosis. The results revealed various chromosomal abnormalities including laggards, stickiness, vagrant chromosomes, binucleated cells, nuclear lesions, giant cells and c-mitosis at different level of treatment. On the whole, aberrations were increasing with the increasing doses along the positive control. In comparison, chili crop had higher level of aberrations depicting the higher chromosomal changes. Lower mitotic index (MI) with increasing level of doses was also describing the hampered cell division due to increased metal stress. The study is showing that the cell division was ceased with increasing metal stress thus increasing the rate of cell aberrations.